The Effect of Performance Allowances on Organizational Culture: The Moderating Role of Leadership Style - Zoniarti, Zoniarti; Nurzam, Nurzam; Irwanto, Tito; Mu'min, Halek (UNIVED Press, 2026)
This study delves into the interactive relationship between performance allowances and organizational culture, with specific reference to the moderating effect of leadership style amongst a sample of 180 PNS and PPPK officers working in city-level offices of the Ministry of Religious Affairs. Using a cross-sectional survey design and Partial Least Squares Structural Equation Modeling (PLS-SEM), this research assesses hypotheses informed by social exchange theory and contingency theory. Performance allowances are found to impact organisational culture substantially (β = 0.169, p < 0.05); however, such an impact is mainly moderated by leadership style, which shows no direct effects. Performance allowances significantly impact leadership style (β = 0.785, p < 0.001), and the latter has a strong impact in turn on organisational culture (β = 0.752, p < 0.001). Leadership style's moderating effect on the relationshipbetween performance allowances and organisational culture is statistically significant (β = 0.050, p < 0.05), and implies synergistic effects when these two constructs are interactive. The model predicts 67.1% and 61.6% of variance for organisational culture and leadership style, respectively. These findings enrich the literature on compensation by presenting leadership behaviour as the overriding mechanism by which performance-based compensation impacts organisational culture and so implying that integrated interventions combining compensation systems and leadership development initiatives may result in superior cultural transformation outcomes.